Annual Plan 2001-2002 Maharashtra State Part II - Planning Commission (Planning Commission, 2001)
Annual Plan, 2001-2002-Maharashtra State Abstract Statement showing sub-sector wise outlay and expenditure Abstract Statement indicating Outlay and Expenditure on Centrally Sponsored Programmes Tribal Sub-Plan Outlay and Expenditure Annual Plan, 2001-2002 Special Component Plan Outlay and Expenditure Annual Plan, 2001-2002 Head of Development Outlay and Expenditure Annual Plan, 2001-2002 20-Pont Programme-Outlays and Expenditure Details Statements of Schemes Included in the Annual Plan 2001-2002 Maharashtra State Physical Targets and Achievements.
Planning Department, Government of Maharashtra